Application of Upcycled Jeans and Macramé Techniques in Edgy Balataraṅg Menswear Designs - Amelia, Dhea; Kusumastuti, Adhi (Journal of Creativity Student, 2025)
The fashion industry significantly contributes to environmental pollution through high textile waste, necessitating more sustainable design approaches, such as upcycling. This study aimed to explore the application of upcycled jeans and macramé techniques in the edgy menswear Balataraṅg and to evaluate its feasibility from technical, aesthetic, and functional perspectives. The research employed a practice-based research approach comprising concept exploration, design development, product realisation, and evaluation through feasibility testing by expert panellists. The findings indicate that upcycled jeans establish a strong visual character through texture and colour exploration, while macramé techniques enhance visual depth and design dynamism. Feasibility testing yielded scores of 91.67% for design, 93.33% for sizing, 80% for sewing techniques, 93.33% for aesthetics, 93.33% for garment performance, and 91.67% for distinctiveness, categorising the Balataraṅg menswear design as highly feasible, with sewing techniques rated as possible. Overall, the study concluded that integrating upcycled jeans and macramé techniques supports the Development of sustainable, distinctive menswear that remains relevant to contemporary fashion trends.